Interventions to Improve the Response of Professionals to Children Exposed to Domestic Violence and Abuse: A Systematic Review. (29th June 2015) - Turner, William; Hester, Marianne; Broad, Jonathan; Szilassy, Eszter; Feder, Gene; Drinkwater, Jessica; Firth, Adam; Stanley, Nicky
Abstract : Exposure of children to domestic violence and abuse (DVA) is a form of child maltreatment with short‐ and long‐term behavioural and mental health impact. Health care professionals are generally uncertain about how to respond to domestic violence and are particularly unclear about best practice with regards to children's exposure and their role in a multiagency response. In this systematic review, we report educational and structural or whole‐system interventions that aim to improve professionals' understanding of, and response to, DVA survivors and their children. We searched 22 bibliographic databases and contacted topic experts for studies reporting quantitative outcomes for any type of intervention aiming to improve professional responses to disclosure of DVA with child involvement. We included interventions for physicians, nurses, social workers and teachers. Twenty‐one studies met the inclusion criteria: three randomised controlled trials (RCTs), 18 pre‐post intervention surveys. There were 18 training and three system‐level interventions. Training interventions generally had positive effects on participants' knowledge, attitudes towards DVA and clinical competence. The results from the RCTs were consistent with the before‐after surveys. Results from system‐level interventions aimed to change organisational practice and inter‐organisational collaboration demonstrates the benefit of coordinating system change in child welfare agencies with primary health care and other organisations. Implications for policy and research are discussed. © 2015 The Authors. Child Abuse Review published by John Wiley & Sons Ltd. 'We searched 22 bibliographic databases and contacted topic experts' Key Practitioner Messages: We reviewed published evidence on interventions aimed at improving professionals' practice with domestic violence survivors and their children. Training programmes were found to improve participants' knowledge, attitudes and clinical competence up to a year after delivery. Key elements of successful training include interactive discussion, booster sessions and involving specialist domestic violence practitioners. Whole‐system approaches aiming to promote coordination and collaboration across agencies appear promising but require funding and high levels of commitment from partners. 'Training programmes were found to improve participants' knowledge, attitudes and clinical competence up to a year after delivery'